Building Competitive Advantage through Knowledge Sharing and Learning Organization with Innovative Work Behavior as Variables Mediation in the Modern Retail Industry - Joelianti Dwi Supraptiningsih; Pristanto Ria Irawan (Global Research Collaboration, 2026)
The increasing intensity of competition in the modern retail industry requires organizations to develop sustainable competitive advantages through effective knowledge management and organizational learning capabilities. This study aims to examine the effects of Knowledge Sharing and Learning Organization on Competitive Advantage, with Innovative Work Behavior serving as a mediating variable. A quantitative research design was employed using a survey method involving 300 employees working in modern retail companies in Bekasi City, Indonesia. Respondents were selected through purposive sampling based on predefined criteria, including a minimum of one year of work experience and direct involvement in operational activities. Data were collected using a structured questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0. The findings reveal that Knowledge Sharing has a positive and significant effect on Innovative Work Behavior, while Learning Organization also positively influences Innovative Work Behavior. Furthermore, Knowledge Sharing and Learning Organization were found to have direct positive effects on Competitive Advantage. However, Innovative Work Behavior did not significantly affect Competitive Advantage and failed to mediate the relationships between Knowledge Sharing, Learning Organization, and Competitive Advantage. These results suggest that organizational competitiveness in the retail sector is primarily driven by effective knowledge exchange and continuous learning capabilities rather than by employee innovation alone. The study contributes to the literature by extending the understanding of how organizational knowledge resources and learning capabilities directly create competitive advantage in service-oriented industries. From a practical perspective, the findings highlight the importance of strengthening knowledge-sharing practices, collaborative learning cultures, and organizational learning systems to enhance long-term competitiveness. Future research is encouraged to incorporate additional organizational variables and explore different industrial contexts to further explain the mechanisms through which organizational capabilities contribute to sustainable competitive performance.